Zimbabwe’s "Capturing a Fading National Memory project": an evaluation and reconsideration - Dombo, Sylvester (Southern Journal for Contemporary History, 2019)
In 2004, the government of Zimbabwe launched the Capturing a Fading National Memory project whose aim was to collect and preserve memories of the 1896/7 uprisings and the liberation struggle of the 1970s. This project was spearheaded by the National Archives of Zimbabwe in collaboration with the National Museums and Monuments of Zimbabwe, and the History Department at the University of Zimbabwe. This article is about the politics of memory and the memorialisation of the liberation struggle in Zimbabwe. It argues that the history of the liberation became important in the post 2000 period in Zimbabwe characterised by economic collapse and political crisis. It feeds into the broader debate on the politics over the control of the past and how that past was deployed in the present to validate the elite’s claim to power while at the same time excluding those that were deemed to be sell-outs.